Design of Miniature Snack Vending Machine Based on Internet of Things - Mukti, Feriyanando Anggawa; Darmono, Hendro; Hidayati, Nurul (Politeknik Negeri Malang, 2024)
Automatic sales machines or vending machines that already exist in Indonesia generally only sell snacks and soft drinks. The lack of vending machines in hotels is due to the high cost of purchasing a vending machine. The average shopping center, hotel, office, and other places in Indonesia still use vending machines with paper money and coin payments. The use of RFID tag cards as a means of payment on snack vending machines is still vulnerable if not given a password or the like for security. The testing parameters in this study are fingerprint sensor accuracy, RFID Reader Visiting, Database connectivity testing on the website, ESP32 testing to the database, and testing the entire system. Fingerprint sensor accuracy testing is done by taking 10 fingerprint samples that have not been registered. The fingerprint sensor works well. RFID testing is done by measuring the maximum distance the RFID Reader can read RFID tags using 3D print barrier with a thickness of 1cm. RFID Reader can read RFID Tags with a maximum distance of 3cm. Database connectivity testing on the website is done to find out whether communication between the database and the web vending machine snack goes well. The results of testing esp32 to the database took 2 tests, namely buyer id testing and balance testing. In the esp32 test to the database the system runs well and correctly. Overall the miniature snack vending machine system runs correctly as designed.